2007
DOI: 10.1074/jbc.m704846200
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an Analog-sensitive Syk Tyrosine Kinase for the Study of Signaling Dynamics from the B Cell Antigen Receptor

Abstract: The Syk protein-tyrosine kinase is an essential component of the signaling machinery that couples the B cell receptor for antigen to multiple downstream signal transduction pathways. Syk is phosphorylated and activated rapidly and transiently following receptor engagement, but many signaling events, such as the activation of transcription factors occur over the course of several minutes or hours. To investigate a role for the continued activation of Syk in these processes, we generated an analogsensitive mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…3B) The OR-gate behavior of Syk may help to explain recent findings that Syk activity is maintained over time after transient activation of the B cell receptor. Many signaling events after BCR ligation are rapidly reversed, but it has recently been found that Syk activity is required for more than 1 h to induce activation of NFAT (nuclear factor of activated T cells) transcription (33). Furthermore, sustained Syk activity has also been linked to store-operated Ca 2ϩ entry, which is important for longer term signaling events (12).…”
Section: Discussionmentioning
confidence: 99%
“…3B) The OR-gate behavior of Syk may help to explain recent findings that Syk activity is maintained over time after transient activation of the B cell receptor. Many signaling events after BCR ligation are rapidly reversed, but it has recently been found that Syk activity is required for more than 1 h to induce activation of NFAT (nuclear factor of activated T cells) transcription (33). Furthermore, sustained Syk activity has also been linked to store-operated Ca 2ϩ entry, which is important for longer term signaling events (12).…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA for Syk-EGFP(R428Q/M429L/M442A) (Syk-AQL-EGFP) was amplified by PCR from the corresponding EGFP-N2 (Clontech) construct (32) and cloned into the Tet-inducible lentiviral vector pLVX-Tight-Puro (Clontech). Lentiviral particles were packaged in HEK293T cells.…”
Section: Methodsmentioning
confidence: 99%
“…Syk is rapidly phosphorylated and activated upon BCR engagement, but its continued activity is required for B cell development and differentiation [39,40]. Activated Syk can move from plasma membrane to other cellular compartments and phosphorylate critical substrates such as BLNK for B cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%